The Development of Students Worksheets Based on Outdoor Learning in Straight Motion Material for X Grade of Senior High School - Widia Hardiyanti; Zulhelmi Zulhelmi; Mitri Irianti (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2021)
Outdoor Learning-based physics student worksheets are task sheets that must be done by students that contain instructions for activities that will be used outside the classroom. This research aims to develop a valid physics worksheet based on outdoor learning on the material of straight motion for class X SMA. The type of research used is Research and Development (R&D) based research with a 4-D model design consisting of 4 stages of development, namely Define, Design, Develop, and Disseminate. Validation is carried out at the development stage by 3 validators who are experts and experienced in their fields and have experience. The instrument of this research is an assessment sheet in the form of a checklist. This research uses two types of data collected, namely quantitative data obtained from the score of the validation sheet assessed by the validator and student responses, while the qualitative data is in the form of criticism and suggestions from the validator on the product developed and a description of the implementation of product trials. Data analysis used descriptive analysis by calculating the index of each indicator used to determine the validity of the developed student worksheets. The results of this research provide an outdoor learning-based physics worksheet product which was developed on straight motion material which was declared valid from the presentation, linguistic, and graphic aspect with high and very high categories, so it was feasible to use in learning to support the teaching and learning process so that it became better.